IMPLEMENTASI KERJASAMA PENEGAKAN HUKUM ANTARA INDONESIA DAN AUSTRALIA DI BIDANG PENYELUNDUPAN ORANG - Wahyuningtyas, Ririn; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study describes the implementation of cooperation between Indonesia with Australia in the field of rule of law in the matter of people smuggling. Law enforcement cooperation agreements exist on Lombok on November 13, 2006. Indonesia as a transit Country people smuggling to Australia destinations.Based on the terms of Indonesia and Australia are facing the same threats, namely in the form of people smuggling crimes.The authors obtained data from journals, official documents, theses, books, the internet to analyze the implementation of law enforcement cooperation in the field of smuggling people between Indonesia with Australia. Theoretical framework the author use in research this is the realist perspective, theory of transnational crime from Monica Massari and Gustavo Cano, and the theory of cooperation from K. j. Holsti.Implementation of law enforcement cooperation in the field of people smuggling between Indonesia with Australia that is through dialogue, consultation and cooperation in capacity building of law enforcement, operating together in intensifying cooperation between police forces, cooperation between the institutions of Indonesia and Australia.Keywords: Treaty of Lombok, Indonesia, Australia, people smuggling, law enforcement